2020
DOI: 10.1038/s41467-020-17418-8
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction-based highly sensitive CRISPR off-target validation using target-specific DNA enrichment

Abstract: CRISPR effectors, which comprise a CRISPR-Cas protein and a guide (g)RNA derived from the bacterial immune system, are widely used for target-specific genome editing. When the gRNA recognizes genomic loci with sequences that are similar to the target, deleterious mutations can occur. Off-target mutations with a frequency below 0.5% remain mostly undetected by current genome-wide off-target detection techniques. Here we report a method to effectively detect extremely small amounts of mutated DNA based on predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…Compared to those DMRT1 knockout chickens, the growth retardation and low survivability shown in this study may not be caused by DMRT1 disruption. Instead, it could be caused by an off‐target effect, as reported in previous genome editing studies 50–53 . In our whole‐genome sequencing analysis, variants near predicted off‐target sites were detected, and it may cause the difference, although no off‐site mutation was found at predicted potential off‐sites.…”
Section: Discussionsupporting
confidence: 64%
“…Compared to those DMRT1 knockout chickens, the growth retardation and low survivability shown in this study may not be caused by DMRT1 disruption. Instead, it could be caused by an off‐target effect, as reported in previous genome editing studies 50–53 . In our whole‐genome sequencing analysis, variants near predicted off‐target sites were detected, and it may cause the difference, although no off‐site mutation was found at predicted potential off‐sites.…”
Section: Discussionsupporting
confidence: 64%
“…Given that off-target effects are a major drawback of the CRISPR/Cas9 system ( 35 ), we verified MAT2A’s effect in J-Lat 9.2 cells by knockdown experiments with shRNA lentiviruses. Western blot showed that the MAT2A protein was efficiently knocked down by shMAT2A-1 and shMAT2A-2 as compared to the control shRNA (shLacZ) ( Figure 2E ).…”
Section: Resultsmentioning
confidence: 88%
“…The cells were disrupted by sonication on ice for 3 min, and the cell lysates were separated by centrifugation at 20,000 × g for 10 min. The purification process was carried out as previously described 18 . Each purified SpCas9 and FnCas9 protein was replaced with a Centricon filter (Amicon Ultra) as a storage buffer [200 mM NaCl, 50 mM HEPES (pH 7.5), 1 mM dithiothreitol (DTT), and 40% glycerol] for long-term storage at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Nested PCR (denaturation at 98°C for 30 s, primer annealing at 62°C for 15 s, and elongation at 72°C for 15 s, 35 cycles) was performed to conjugate adapter and index sequences to the amplicons. All targeted amplicon sequencing and data analysis were performed as suggested in a previous study 18 .…”
Section: Methodsmentioning
confidence: 99%